(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to be an initial step to introduce the culture of political debate and the need to learn its principles and adopt it as an important method of the globally used methods to confront crises by gaining consensus and support and it’s an effective and smooth method of persuasion. The importance of this study is that political debate has a role at crises management according to the high increasing, diversity of crises, and their large number of negative consequences. Crisis management is considered as a method of dealing with existing conflicts, and an aspect of humanitarian dealing with emergency situations, also studying the role of the political debate method followed by the mission of Syrian Arab Republic to the United Nations to confront the war that was launched against Syria, and help to gain international support and public opinion due to the importance of political debate in containing the international crisis by making the views closer, and clarifying the facts to the international community due to its directness, clarity and transparency away from political escalation. The descriptive analytical method was relied on in order to narrate and track the facts and events of the course of the political situation in the international arena under the war imposed on Syria at all levels, and to analyze and describe them systematically, in addition to research on the events and backgrounds of the war on Syria, also the historical approach was relied to study the history and methods of the debate, its types and the role that plays to make the work of diplomatic missions successful and to study the experiences of the countries that used debate method.